Maqāṣidī Models for an “Islamic” Medical Ethics: Problem-Solving or Confusing at the Bedside? (American Journal of Islam and Society, 2022)
The maqāṣid al-shari‘ah are championed as tools to address contemporary societal issues. Indeed, it is argued that maqāṣidbased solutions to present-day economic, political, and cultural challenges authentically bridge the moral vision of Islam with modernity.  Advocates also stress that maqāṣidī models overcome shortcomings within fiqh-based strategies by bypassing their over-reliance on  scriptural and legal hermeneutics, their dated views on social life, and their analytic focus on individual action. Herein I critically analyze efforts to bring maqāṣidī thinking to the clinical bedside. Specifically, I describe how leading thinkers such as Profs. Gamal  Eldin Attia, Tariq Ramadan, Omar Hasan Kasule, and others build maqāṣid frameworks for medical ethics by expanding upon Imam  Abū Ishāq al-Shāṭibī’s maqāṣid al-sharīʿah theory. I categorize these varied approaches into three types (field-based redefinition, conceptual extension, and text-based postulation) and detail how each sets up a specific method of medical ethics deliberation.  Moving from the theoretical to the practical, I use a test case, a 19-weeks pregnant “brain dead” Muslim woman, to ascertain the goals of care and the respective moral responsibilities of her husband and the treating Muslim clinician using the three models. Next, I discuss the merits and pitfalls of each proposed solution and comment on how these match up with extant fiqh. To close the paper, I comment on the place of maqāṣidī thinking in Muslim engagement with contemporary biomedicine, contending that such frameworks are presently too underdeveloped for medical ethics deliberation at the bedside. Indeed, without further elaboration from theorists,  appeal to the maqāṣid in medical ethics deliberation may provide clinicians, patients, and other stakeholders with ambiguous, incomplete, impractical, or otherwise problematic answers.